PEMANFAATAN KULIT PISANG ( MUSA PARADISIACA) SEBAGAI PEMBUATAN BATERAI PADA PRAKTIKUM SEL ELEKTROKIMIA DI MAN 1 PEKANBARU - ranti yanasari; fitri refelita (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
The research on the application of banana skin (Musa Paradisiaca) has been done as a production of natural battery paste.  This research is aimed at to see the voltage, light flame, and the endurance that are produced by two varieties of the banana skins. the banana skins that are utilized are the skins of Berangan banana and Kepok banana. Each of the mass samples is 5 grams. In the research, the addition of salt is performed. The KCl salt with different mass is conducted: 0.75; 1; 1.25; 1.5; 1.75 and 2 grams until it reached 1.5-1.8 volts of voltage. The addition of salt is done to gain a more optimum voltage. The result indicates that the Berangan banana skin has better voltage and endurance comparing to Kepok banana. The voltage that is generated by Berangan banana skin is 1.17 volts with the endurance time of 4 days. After being added with the salt, the voltage increased to 1.54 volts and the endurance of 11 days. For Kepok banana, it is generated 1.00 volts with the endurance time of 3 days. After the salt addition, the voltage increases to 1.52 volts with the endurance of 7 days. The questionnaire of teacher’s evaluation about the research result as learning sources at voltage cells practicum gives a cumulative score of 93.75% which is categorized very good.                                                                                    Keywords: banana skin battery paste, battery, banana skin, voltage, electrolyte.